Studies on Homalomeneae (Araceae) of Borneo XXIII: a new rheophytic species of Homalomena (Punctulata Clade) from the Tau Range, Sarawak - Wong, Sin Yeng; Boyce, Peter C. (John Wiley & Sons Ltd, 2020)
Homalomena cataractae is described and illustrated as a new species of Steenisian rheophyte belonging to the Homalomena punctulata-clade from the Tau range, Central Sarawak. A key to the species of the Homalomena punctulata-clade is provided.